Maternal mortality and the implementation of maternal health policies in Zamfara state: challenges and issues - Mohammed Maiwada, Abdullahi; A. Rahman, Nor Azlina; Abdul Rahman, Suzanah; Mamat, Nik Mazlan; Baba, Tukur (International Standard Research Publishing, 2015)
The Nigerian health system operates within the federal design of its political system. The 1988 National Health Policy revised in 1996 and 2004 lays out the different functions within the system. The Federal Ministry of Health is responsible for defining the overall policy framework for the health system of the whole country. There is a wide geographical variation on maternal mortality in Nigeria, with the north having a far higher rate compared to the south. The North-west zone has one of the highest figures of 1,549/100,000 almost ten times that of the south-western zone (165/100,000). The rural area, where most of Nigerians live, has a higher maternal mortality ratio (828 deaths per 100,000 live births) compared to the urban areas (351 maternal deaths per 100,000 live births). The leading causes of maternal mortality were eclampsia, sepsis, postpartum haemorrhage, antepartum haemorrhage, unsafe abortion, obstructed labour and heart failure. Also several intermediate social and cultural factors account for many of these deaths. In the face of these challenges, there have been efforts on the part of the Government of Nigeria and states to improve the health status of women and children. Data for this study were collected through review of secondary data; facilities based approached and questionnaire administration. The results of the study showed that there are several maternal health policies launched in Zamfara State and Nigeria but are faced with several challenges and issues of implementation. Zamfara State has put in place several interventions policies and programmes in order to improve the maternal health situation in the state and reduce maternal mortality. Many of the respondents interviewed are aware of some of the policies or their implementation. However, respondents are of the opinion that there are inadequate staff and equipment to cater for the maternal health services in the state. It is concluded that maternal mortality in Zamfara State still remain high and even higher than the national average of 576 according to the Nigeria Demographic and Health Survey of 2013 despite the implementation of some of these policies.